Endogenously Proportional Bargaining Solutions - Ismail Saglam (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
This paper introduces a class of endogenously proportional bargaining solutions. These solutions are independent of the class of Directional solutions, which Chun and Thomson (1990a) proposed to generalize (exogenously) proportional solutions of Kalai (1977). Endogenously proportional solutions relative to individual i are characterized by weak Pareto optimality and continuity together with two new axioms that depend on the pairwise total payoff asymmetry of the bargaining problem with respect to each pair involving individual i. Each of these solutions satisfies the basic symmetry axiom and also a stronger axiom called total payoff symmetry.
Keywords: C71; C78; 330; Cooperative bargaining; proportional solutions; symmetry; Kooperatives Spiel; Verhandlungstheorie